Education in Emergency: A Climate Change Adaptation Agendum Towards the Socio-Economic Propagation of Bangladesh - Shoeb-Ur-Rahman, Muhammad; Rahman, Muhammad Ishaq Ur; Hossain, Md. Shakib (Social Science Research Network, 2013)
Both the scientific and negotiating community has recognized Bangladesh as one of the most vulnerable countries to Climate Change effect which in future is likely to face more frequent climatic adversities. This paper emphasizes on putting the theme of ‘Education in Emergency’ in all climate change adaptation efforts in the country which can enable it to safeguard country’s important education sector during any disaster or in the recovery phase. Education has received inconsiderable amount of importance in those efforts and ultimately encompassed all the spheres of social, emotional, cognitive and physical ground which decelerate multifarious predicaments and adversities. In preparing this paper the authors highly rely on secondary sources of data. In the era of globalization, a vast number of populations remain untouched or being detracted from the light of education. It is particularly fact for country like Bangladesh where natural calamity is an incessant event due to the intrusion of globalization. Bilateral, multilateral, regional and global affiliation and association can be undertaken to the depletion of hindrances. Besides, substantial and congruous strategies, plans, policies and programs within the internal infrastructure may assist to mitigate this endanger and also comply with the commitment of education for all even in the cataclysm. For accomplishing responsiveness and flourishing prowess, an integrating approach to the management of Education in Emergency (EiE) requires coordination and collaboration among government departments or ministries and agencies, designing and upgrading courses (including issues like Need for Sustainable Development and Actions for Environment Protection, Environmental Management Tools & Environmental Assessment, Environment Pollution Management, Progress in Environmental Science, International Environment Laws etc.), as well as superior and immaculate information technology to resolve this consternation and vulnerability. Propitious and admissible approaches can ensure eco-balance and sustainable socio-economic development in a vulnerable country like Bangladesh with a proper accentuation on education in emergency. This paper will be highly helpful for policy makers both in private and public sectors to ensure sound education opportunity in the highly disaster prone i.e., coastal areas. However, this piece of effort might also cut attention of the human rights workers.
Keywords: C:Bangladesh; _z:class:countries; _z:class:themes; oa:sdg:13 Climate action; oa:topic:T10747 Community Resilience to Natural Disasters; openalex:import; openalex:yes

Education in Emergency: A Climate Change Adaptation Agendum Towards the Socio-Economic Propagation of Bangladesh - Shoeb-Ur-Rahman, Muhammad; Rahman, Muhammad Ishaq Ur; Hossain, Md. Shakib (Social Science Research Network, 2013)
Both the scientific and negotiating community has recognized Bangladesh as one of the most vulnerable countries to Climate Change effect which in future is likely to face more frequent climatic adversities. This paper emphasizes on putting the theme of ‘Education in Emergency’ in all climate change adaptation efforts in the country which can enable it to safeguard country’s important education sector during any disaster or in the recovery phase. Education has received inconsiderable amount of importance in those efforts and ultimately encompassed all the spheres of social, emotional, cognitive and physical ground which decelerate multifarious predicaments and adversities. In preparing this paper the authors highly rely on secondary sources of data. In the era of globalization, a vast number of populations remain untouched or being detracted from the light of education. It is particularly fact for country like Bangladesh where natural calamity is an incessant event due to the intrusion of globalization. Bilateral, multilateral, regional and global affiliation and association can be undertaken to the depletion of hindrances. Besides, substantial and congruous strategies, plans, policies and programs within the internal infrastructure may assist to mitigate this endanger and also comply with the commitment of education for all even in the cataclysm. For accomplishing responsiveness and flourishing prowess, an integrating approach to the management of Education in Emergency (EiE) requires coordination and collaboration among government departments or ministries and agencies, designing and upgrading courses (including issues like Need for Sustainable Development and Actions for Environment Protection, Environmental Management Tools & Environmental Assessment, Environment Pollution Management, Progress in Environmental Science, International Environment Laws etc.), as well as superior and immaculate information technology to resolve this consternation and vulnerability. Propitious and admissible approaches can ensure eco-balance and sustainable socio-economic development in a vulnerable country like Bangladesh with a proper accentuation on education in emergency. This paper will be highly helpful for policy makers both in private and public sectors to ensure sound education opportunity in the highly disaster prone i.e., coastal areas. However, this piece of effort might also cut attention of the human rights workers.
Keywords: C:Bangladesh; _z:class:countries; _z:class:themes; oa:sdg:13 Climate action; oa:topic:T10747 Community Resilience to Natural Disasters; openalex:import; openalex:yes

Climate Change Education Curriculum for Nigeria Tertiary Education System - Dada, Abdullahi Aliyu; Muhammad, Umar (Sokoto Educational Review, 2014)
The paper attempted to propose a Climate Change Education Curriculum that is conceived to provide a clear understanding of the Climate Change phenomenon for students in Tertiary institutions in Nigeria. Nobody is left in doubt of the relevance of climate change education in Nigeria tertiary education system. Tertiary educational institutions are expected to play a proactive role in proffering solutions to climate change challenges facing Nigeria. What needs to be done is to harness resources toward putting in place a well-articulated climate change education curriculum that should provide requisite information/knowledge and skills for future leaders. Thus, it is recommended that cogent policies need to be developed to ensure that climate change education is fully integrated into tertiary education system in Nigeria; that climate change education curriculum should be offered either as a standalone specialized course or integrated within other courses; and professional development support be provided to educators so as to be able to deliver effectively and also to be able to develop relevant teaching materials on climate change that could stand the test of time.
Keywords: C:Nigeria; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T13530 Climate Change and Environmental Impact; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found